Determination and Freedom in Creation Mediated by Sign Systems - Duarte, Newton [UNESP]; Silva, Efrain Maciel E; Anjos, Ricardo Eleutério Dos (Universidade Federal do Rio Grande do Sul, 2021)
This article examines the relationship between determination and freedom in the human act of creation mediated by the use of sign systems. To this end, an approximation is made between György Lukács’ philosophical-ontological reflection on the dialectic between teleology and causality in work activity and analysis carried out by Lev Vigotski on the importance of sign systems for human psychic development. It is concluded that creation involves complex relations between the freedom of the subjects and the socio-cultural determinations.

Cet article examine la relation entre la détermination et la liberté dans l’acte humain de création médiée par l’utilisation des systèmes de signes. À cette fin, une approximation est faite entre la réflexion philosophique-ontologique de György Lukács sur la dialectique entre la téléologie et la causalité dans l’activité de travail et les analyses développées par Lev Vigotski sur l’importance des systèmes de signes pour le développement psychique humain. On en conclut que la création implique des relations complexes entre la liberté des sujets et les déterminations socioculturelles.
Détermination et Liberté dans la Création Médiée par les Systèmes de Signes
Keywords: Creation; Creativity; Freedom; György Lukács; Lev Vygotsky